El despertar de la infografía en la prensa escrita: el caso de La Voz de Galicia - Calvo Ferreiro, María Dolores; Otero López, María Luisa; López García, Xosé (Estudios sobre el Mensaje Periodístico, 2008)
In this article we are going to approach the study of a way of expression that has more prestige and presence in mass media every day: the infographics. We will concentrate on a historical fact: 1st Persian Gulf War, as first worldwide event happened when computing starts settling down in newspaper editorial offices; and on a print newspaper: La Voz de Galicia, as a publication of reference in Spain and, especially, in Galicia. On next pages, we are going to study the characteristics, structure, composition, content and functions of the infographics done at that time and we check too if, like happened in other Spanish newspapers, 1st Persian Gulf War was the engine that favoured the development of infographics in La Voz de Galicia.
Keywords: Infographics; La Voz de Galicia; Persian Gulf War; Informative graphics